Grundzüge der Außereuropäischen Christentumsgeschichte: Asien, Afrika, und Lateinamerika 1450–2000 (Main Features of the Non-European History of Christianity: Asia, Africa, and Latin America, 1450–2000) - Ward, Kevin (International bulletin of mission research, 2024)
Professor Klaus Koschorke’s pioneering work Grundzüge der Außereuropäischen Christentumsgeschichte: Asien, Afrika, und Lateinamerika 1450–2000 (Main features of the non-European history of Christianity: Asia, Africa, and Latin America, 1450–2000) provides an overview of the historical development of Christianity in the Global South between 1450 and 2000. Koschorke emphasized the “polycentric” nature of Christianity—the fact that, for the gospel to be successful, it must become deeply embedded in the local cultures it encounters, producing forms of Christianity that are distinctive from those of Europe or North America, and in which indigenous evangelism, theology, and discipleship flourish. Koschorke also highlights the importance of relationships between the churches of South America, Asia, and Africa, the Black Atlantic, networks of co-operation throughout the Indian and Pacific Oceans that are as important as Western missionary movements in identifying Christianity as a world religion.